The roles of local communities in forest fire management in Thailand : case study at Huay Kha Khaeng Wildlife sanctuary in Uthai Thani province of Thailand - Thawatchai, Vierra (Faculty of Social Sciences, 2002)
Forest fire occurs both inside and adjacent to the wildlife sanctuary (buffer zone). The major causes of forest fire int he study area were due to the activities of the communitties living within or sorrounding the buffer zone, as well as wildlife hunting, tourism activities, and wandering monk. The goal of this study was to present the roles of communities on forest fire management settled in the buffer zone adjacent to Huay Kha Khaeng Wildlife Sanctuary, Uthai Thani Province, Thailand. The attemps of this study include the determination of the interest of the local communities in untilizing and conserving the forest, evaluating their readlines as well as capability in participation of forest management.